Contemporary marketing concepts and conceptual thoughts: a knowledge-building approach - Rahman, Muhammad Sabbir; Osman , Bin Mohamad; Md. Ashraful , Azam Khan; Mrs. Yunita , Agustian Minjalnis (TIJ Research Publications PTE. LTD, 2015)
The practice of Marketing is the engine of all types of business. This book is entitles ‘Contemporary Marketing Concepts and Conceptual Thoughts- A knowledge-Building Approach ’, its contents draw heavily in developing conceptual framework, a term which has produced from the imagination of the academics. The aim of this book is to provide readers with the conceptual information about the thought provoking the issues of marketing. This book may be used in research methods course with a great success in view of writing literature review. All the chapters in the book include conceptual framework of the contents discussed, emphasizing the need for the Marketing research students. We expect that students andinstructors alike will enjoy this edition. As students should become efficient Marketing researchers, assisted by the knowledge and skills acquired by the study of this book.